Financial management skills of nurse managers in the Eastern Region of Ghana - Yennuten Paarima; Atswei Adzo Kwashie; Adelaide Maria Ansah Ofei (Elsevier, 2021)
Background: Ghana's healthcare sectors are faced with several financial challenges due to increased funding cuts and delayed reimbursement from the National Health Insurance Authority (NHIA). This has necessitated nurse manager to build financial management skills to enable them to lead in the provision of effective and efficient care while reducing cost. This demands adequate knowledge and skills in financial management. The study examined the financial management skills of nurse managers at the unit level. Methods: A quantitative approach using a cross-sectional design was employed using the census approach to collect data from 121 nurse managers in ten hospitals in the Eastern Region of Ghana. Data analyses were performed using descriptive and linear regression analyses. Findings: Nurse managers showed a moderate level of knowledge and skills in financial management. Age, gender, qualification, experience as a nurse manager, and training in management jointly predicted nurse managerss' financial management (R2 = 0.12, p = 0.029). However, only training in management significantly contributed to the financial skills of nurse managers. Conclusion: Nurse managers play a significant role in the financial management of hospitals but have inadequate knowledge, skills, and competence in financial management. Recommendations include well-structured training and education on financial management using a multidisciplinary approach to enable nurse managers to gain the required knowledge and skills. Continuous experiential learning and mentorship programs should be developed for nurses before the assumption of management positions.